Economic Aspects of Mandatory Retirement: The Canadian Experience - Reid, Frank (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
Economie impacts of eliminating mandatory retirement are a crucial aspect of the Charter of Rights arguments concerning the «reasonableness» of age discrimination. Evidence suggests that the number of employees who would workpast normal retirement age in any given year is only a fraction of one percent of the labour force. Eliminating mandatory retirement would consequently have minimal impact on job opportunities for youth and personnel practices concerning evaluation of employees. Actuarial adjustment of private pension plans to accommodate a flexible retirement age is only a minor administrative matter and has already been implemented in some Canadian jurisdictions